STUDENTS' LEVEL OF CONFIDENCE IN LEARNING FRONT ROLL FLOOR GYMNASTICS AT 1 PURWADADI STATE HIGH SCHOOL - Naufal Fajri Ramadhani; Citra Resita; Aria Kusuma Yuda (Journal Physical Education, Health and Recreation, 2022)
Naufal Fajri Ramadhani with the research title "Students' Level of Confidence in Learning Front Roll Floor Gymnastics at 1 Purwadadi State High School 1". Physical Education, Health and Recreation Study Program. Faculty of Teacher Training and Education. Singaperbangsa Karawang University.This study aims to determine how high students' confidence in learning front roll floor gymnastics at 1 Purwadadi State High School is in the 2022/2023 teaching. This study uses an approach when viewed from the type of research data presented. The method in this is a survey research using a questionnaire. The results of this study on the level of student confidence in learning front roll floor gymnastics at 1 Purwadadi State High School for the academic year 2022/2023 obtained the lowest score (minimum) 28, the highest score (maximum) 116, average (mean) 83.9, middle value (median) 80, frequently occurring value (mode) 80, standard deviation (SD) 19.3. Based on the results of data analysis and discussion, we can conclude that the interest of class X students in learning swimming at SMA Negeri 1 Pagaden for the academic year 2021/2022 is in the "medium" category by 30% (12 students), "high" by 10% (4 students), "low" by 45% (18 students), "deficient" by 15% (6 students), and "very high" by 0% (0 students)